PENGARUH FAKTOR PREDISPOSISI PENDUKUNG DAN PENDORONG IBU TERHADAP PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PANGIRKIRAN KECAMATAN HALONGONAN KABUPATEN PADANG LAWAS UTARA TAHUN 2015 - Harahap, Ica Fauziah; Siagian, Albiner; Tampubolon, Elmina (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Maternal breast feedy is the best nutrition at the early age of the baby's life. Exclusive breastfeeding is given only breast milk for baby without any additional food up to six months old. The Target exclusive breastfeeding in the Health Service of North Padang Lawas District is 85% but the scope of exclusive breastfeeding in the Puskesmas of Pangirkiran in February 2014 amounted to 30.5% and the scope of exclusive breastfeeding in August 2014 amounted to 36.2%. This study was an observational research design with a case-control and the study aims to analyze the influence of predisposing factors  (knowledge,  attitudes), enabling factors (lactation), reinforcing factors (family support, support health workers) loward exclusive breastfeeding in the working area Puskesmas of Pangirkiran Halongonan sub district of Halongonan district of North Padang Lawas. The Population of this research is all breast feedy mothers  who has baby in 6 – 12 months. The sample is 144 people consist of is people in 72 cases and 72 controls. Based on the results of the study indicate the variables of knowledge, attitude, lactation, family support and support health workers influence on exclusive breastfeeding. Expected to health workers in health centers in the Puskesmas Pangirkiran to further improve counseling on exclusive breastfeeding to the public so that exclusive breastfeeding to the baby can be improved.